Order Management System For Restaurant (Omsr) - Tan, Chee Kin (2023)
Food is one of the most essential things that humans need. We need food for energy to carry out our daily routine. However, it is a time-consuming process for placing an order in a restaurant. Moreover, most restaurants today are still using a paper-based ordering method which has a high error rate due to the staff need to have a good memory. Besides, orders may also be lost during the process of delivering among the staff. Hence, the rate of delivering a wrong order is high and customers’ dining experience will also be affected especially during peak hours. Therefore, Order Management System for Restaurant (OMSR) is proposed system to help in dealing with these problems. The main focus of this project is to develop a cancellation ordering application for restaurant with a single click. Three existing ordering applications have been reviewed to achieve this aim and produce a better ordering system with cancellation function at the end of this project. The expected output of this project is an order management system that provides various functions to the user. For instance, the customer can place order, view the order status of placed order, view the order history, provide feedback and cancel their order if it met the constraint via the application developed. On the other hand, the business owner can view customers’ feedback and sales report via the application. Last but not least, the restaurant staff can view customers’ orders and update the status from time to time.